PGE2 displays immunosuppressive effects during human active tuberculosis - Joaquín Miguel Pellegrini (Nature Portfolio, 2021)
Abstract Prostaglandin E2 (PGE2), an active lipid compound derived from arachidonic acid, regulates different stages of the immune response of the host during several pathologies such as chronic infections or cancer. In fact, manipulation of PGE2 levels was proposed as an approach for countering the Type I IFN signature of tuberculosis (TB). However, very limited information regarding the PGE2 pathway in patients with active TB is currently available. In the present work, we demonstrated that PGE2 exerts a potent immunosuppressive action during the immune response of the human host against Mycobacterium tuberculosis (Mtb) infection. Actually, we showed that PGE2 significantly reduced the surface expression of several immunological receptors, the lymphoproliferation and the production of proinflammatory cytokines. In addition, PGE2 promoted autophagy in monocytes and neutrophils cultured with Mtb antigens. These results suggest that PGE2 might be attenuating the excessive inflammatory immune response caused by Mtb, emerging as an attractive therapeutic target. Taken together, our findings contribute to the knowledge of the role of PGE2 in the human host resistance to Mtb and highlight the potential of this lipid mediator as a tool to improve anti-TB treatment.